Improved conceptual framework based on the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) version 3 to assess environmental impacts in Livestock Master Plans - CGIAR Research Program on Livestock (2021)
The first stage, conceptualization and development of a framework for linking economic and environmental assessment models, is complete. Following prioritization, literature and existing environmental models were reviewed. Feed was clearly identified as being the key link between the economic and environmental models.